Development of a Lichens Pocketbook in Low-Level Organism Taxonomy Course - Hasairin, Ashar; Hartono, Adi; Hasim, Hasrina (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2023)
The Lichens Pocketbook is a vital teaching medium in Low-Level Organism Taxonomy courses. It contains conceptual materials to support students' understanding of achieving learning objectives. Therefore, this study aims to determine the results of the assessment and responses of material expert validators on the feasibility of the Lichens Pocketbook; find out the results of assessments and responses of material expert validators on the feasibility of the Lichens Pocketbook; find out the results of the assessment and responses of design expert validators on the feasibility of the Lichens Pocketbook. This pocketbook was developed according to the Thiagarajan (4-D) model, limited up to the development stage. The analysis showed that the developed Lichens Pocketbook was declared feasible based on the material experts' validation with an average value of 92.48% within the excellent feasible categories. The validation results from learning expert validators obtained an average of 83.88% within the excellent and feasible categories. Lastly, the validation results from design expert validators obtained an average value of 90.89% within the excellent and feasible categories. Thus, the developed Lichens Pocketbook can be used in learning. ABSTRAK: Buku saku lichens merupakan media ajar yang penting dalam perkuliahan Taksonomi Organisme Tingkat Rendah. Hal ini dikarenakan, buku saku tersebut memuat rangkaian materi konseptual yang dapat mendukung pemahaman peserta didik dalam mencapai tujuan pembelajaran. Berdasarkan hal tersebut penelitian ini bertujuan untuk mengetahui hasil penilaian dan tanggapan validator ahli materi terhadap kelayakan buku saku pada materi lichens, mengetahui hasil penilaian dan tanggapan validator ahli pembelajaran terhadap kelayakan buku saku pada materi lichens dan mengetahui hasil penilaian dan tanggapan validator ahli desain terhadap kelayakan buku saku pada materi lichens. Buku saku ini dikembangkan menurut model Thiagarajan (4-D) yang dibatasi hingga tahap pengembangan. Hasil validasi dari ahli materi memperoleh nilai rata-rata 92,48 % dengan kategori layak, hasil validasi dari ahli pembelajaran memperoleh nilai rata-rata 83,88 % dengan kategori layak, dan hasil validasi dari ahli desain memperoleh nilai rata-rata 90,89 % dengan kategori layak. Dengan demikian, dapat disimpulkan buku tersebut dapat digunakan dalam pembelajaran.